First International Congress on Adhesion Science and Technology - invited papers : festschrift in honor of Dr. K. L. Mittal on the occasion of his 50th birthday /: festschrift in honor of Dr. K. L. Mittal on the occasion of his 50th birthday. (2023) - Unknown
No abstract available